Relevansi Nusyuz dengan Isu Kontemporer Marital Rape dalam Bingkai Cedaw - Anita Bagaskara Ningrum Diprabawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The study explores the International Convention (CEDAW) as a legal framework for addressing injustice in the protection of marital rape cases. How to involve the interpretation of CEDAW and the analysis of the handling of marital rape in various jurisdictions, to the extent to which it is appropriate or contrary to CEDAW principles. Literature studies with normative approaches are used as research methods, with data analysis using analytical descriptive approaches. This study found that although CEDAW is a key instrument in women’s rights, its implementation varies. Marital rape is not in line with CEDAW principles, there are several influencing factors. that the need for serious treatment of marital rape to achieve CEDAW goals. Although there have been legal efforts such as the Domestic Violence Elimination Act (PKDRT), more attention is needed to the Sexual Violence Elimination Bill (PKS). In criminal law, it is necessary to exploit rape in the household. The research contributes to an understanding of the challenges and efforts to improve the protection of women from marital rape in various jurisdictions.